2016
DOI: 10.1002/adem.201600143
|View full text |Cite
|
Sign up to set email alerts
|

Bone‐Inspired Materials by Design: Toughness Amplification Observed Using 3D Printing and Testing

Abstract: Inspired by the fact that nature provides multifunctional composites by using universal building blocks, the authors design and test synthetic composites with a pattern inspired by the microstructure of cortical bone. Using a high-resolution multimaterial 3D printer, the authors are able to manufacture samples and investigate their fracture behavior in mechanical tests. The authors' results demonstrate that the bone-inspired design is critical for toughness amplification and balance with material strength. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
96
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(100 citation statements)
references
References 49 publications
4
96
0
Order By: Relevance
“…Three‐dimensional printing has proven to overcome many of the limitations and complexities that conventional procedures pose in the design of complex geometries, such as the limited control in the customization of porosity size distribution . A few studies have demonstrated the capabilities of 3D printing in the manufacturing of bone‐like structure, combining good mechanical properties and low density. An interconnected porosity in the printed scaffolds will affect the mechanical properties of the structure but will provide the optimal environment to promote cell adhesion and proliferation .…”
Section: Introductionmentioning
confidence: 99%
“…Three‐dimensional printing has proven to overcome many of the limitations and complexities that conventional procedures pose in the design of complex geometries, such as the limited control in the customization of porosity size distribution . A few studies have demonstrated the capabilities of 3D printing in the manufacturing of bone‐like structure, combining good mechanical properties and low density. An interconnected porosity in the printed scaffolds will affect the mechanical properties of the structure but will provide the optimal environment to promote cell adhesion and proliferation .…”
Section: Introductionmentioning
confidence: 99%
“…
(1 of 10) 1605350 materials exhibiting both excellent loadbearing capacity and fracture resistance, as can be observed from both hard tissues [3][4][5][6][7] (e.g., nacre and bone) and soft tissues (e.g., ligament and tendon), [8][9][10] by combining rigid, brittle components (either inorganic or organic) and soft, organic components into composite materials. Most of these natural materials have highly complex hierarchical architectures existing over multiple length scales, which results in composite properties that far exceed what could be expected from a simple combination of the individual components.
…”
mentioning
confidence: 99%
“…Having tested the crack propagation in homogeneous specimens, we now consider the fracture of heterogeneous materials composed of two constituent materials with very high mismatch in the elastic moduli, such as those occurring in biomaterials or engineering composites reinforced with high strength and high modulus fibers. We first consider a specimen designed to mimic the microstructure of cortical bone, following previous studies [27,28]. It is known that a high modulus mismatch in cortical bone structure causes crack deflection [27,28], which increases the toughness modulus of the material.…”
Section: Tensile Test Of a Bone-inspired Compositementioning
confidence: 99%